Kierunki przekształceń świadomości narodowej Polaków w przededniu wejścia do Unii Europejskiej – pytania badawcze - Wójcik, Stanisław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
The shape ofWestern Europe is settled in principle. For us – the people of Central and Eastern Europe – it is something of a European paradise. The difficulties emerge only in the realm of the philosophy of life and religion, although the West either does not realize these problems or neglects them. Can the candidate states meet the criteria the European Union has established? The following dilemmas should be solved here: as we access the EU in order to obtain forecasted economic and technical benefits, may we have to abandon with time our systems of values that are classical for European and Christian culture? What about the State security and sovereignty? Should we hasten to access the EU given the ruined economy, profound political divisions in Poland and the absence of the majority representation of the Polish society in the government? The attitude of Polish society to the accession to the EU is currently undergoing a transformation. The doubts about its value spread particularly in the provinces where the adverse results of wrong domestic and western economy are most acute. It should be scientifically explained why Western societies, in particular those of smaller states, such as Austria, increasingly complain about the conditions in the EU and actually regret their own accession. French, German and Italian ideologists propagate the creation of a single supranational state out of the whole Europe. This stands in direct opposition to the Polish national consciousness, including the Catholic, cultural and linguistic consciousness, as it is impossible to artificially create a new European nation in such a  short  time.